Chemoenzymatic Synthesis of Sertraline. Issue 4 (17th January 2020) - Marx, Lisa; Ríos‐Lombardía, Nicolás; Süss, Philipp; Höhne, Matthias; Morís, Francisco; González‐Sabín, Javier; Berglund, Per
Abstract : A chemoenzymatic approach has been developed for the preparation of sertraline, an established anti‐depressant drug. Ketoreductases (KREDs) were employed to yield a key chiral precursor. The bioreduction of the racemic tetralone exhibited excellent enantioselectivity (>99 % ee ) and diastereomeric ratio (99:1) at 29 % conversion (the maximum theoretical yield is 50 %) after 7 hours. The resulting ( S, S )‐alcohol was efficiently oxidized to an enantiopure ( S )‐ketone, an immediate precursor of sertraline, by using sodium hypochlorite as oxidant and 2‐azaadamantane N ‐oxyl (AZADO) as organocatalyst. Alternative routes aiming at the direct biocatalytic amination using imine reductases and transaminases were unsuccessful. Abstract : A chemoenzymatic approach has been developed for the preparation of sertraline. Ketoreductases (KREDs) were employed to yield a key chiral precursor. The bioreduction of the racemic tetralone exhibited excellent enantioselectivity (>99 % ee ) and diastereomeric ratio (99:1) at 29 % conversion.